2001
DOI: 10.1248/cpb.49.1395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cetrimide and Ascorbic Acid on in Vitro Human Skin Permeation of Haloperidol.

Abstract: Haloperidol (HP) is given in the treatment of acute psychosis as well as in maintenance therapy to prevent the relapse of the psychosis.1) Long-acting formulations are more meaningful in the maintenance therapy since long-term daily oral dose of 3 to 10 mg of HP 2) may lead to noncompliance. HP decanoate oily injection, the only long acting formulation available at present, has some disadvantages namely; complex dosing schedule while converting from oral therapy to depot therapy, 3) pain at the site of injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
7
0
5
Order By: Relevance
“…Thus, decreased antimicrobial activity of Elaeagnus angustifolia by lysozyme may be related to break down of polyphenolic glycosides (flavonoids). Our study on inactivation of the Elaeagnus angustifolia extract by detergents like Tween 80, Tween 20, Triton X100 and toluene showed that inactivation occurs because these detergents can interact with both proteins and lipids and this interaction is irreversible (14). It is therefore, tempting to propose the presence of a lipid compound which had a potent antimicrobial activity.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, decreased antimicrobial activity of Elaeagnus angustifolia by lysozyme may be related to break down of polyphenolic glycosides (flavonoids). Our study on inactivation of the Elaeagnus angustifolia extract by detergents like Tween 80, Tween 20, Triton X100 and toluene showed that inactivation occurs because these detergents can interact with both proteins and lipids and this interaction is irreversible (14). It is therefore, tempting to propose the presence of a lipid compound which had a potent antimicrobial activity.…”
Section: Discussionmentioning
confidence: 91%
“…Ascorbic acid has been tested for its penetration enhancement properties using haloperidol as a model drug and amber glass Franz-type diffusion cells for the permeation studies. Ascorbic acid did not increase the permeation of the drug but increased the haloperidol solubility in the vehicle, which leads to a concentration-dependent increase in the haloperidol fl ux [90] . The primary capsaicinoid capsaicin was tested to compare its skin penetration-enhancing effects with those of Azone.…”
Section: Novel Penetration Enhancers and Novel Discovery Techniquesmentioning
confidence: 85%
“…Further, cetrimide treatment decreased the absorbance of amide A and amide II bands, probably due to its interaction with keratin. However, no shift in amide I band at 1650 cm -1 was observed, indicating that it failed to produce any change in protein conformation [185].…”
Section: V) Surfactantsmentioning
confidence: 94%